Hydration Behaviour and Characteristics of Binary Blended Metakaolin Cement Pastes - Abah Joseph Apeh (Journal of Building Materials and Structures)
Cement production consume large amount of energy to form clinker and carbon dioxide (CO2) emitted into the atmosphere causing global warming. To mitigate this challenge, the use of Metakaolin (MK) as supplementary cementitious material cannot be over emphasized. This study evaluated the use of Metakaolin (MK) on hydration development of MK--PC blended cements and strength of Mortars. The MK with a Blaine fineness of 7883 cm2/g was used to replace Portland Cement (PC) at a level of 0, 5, 10, 15, 20, 25 and 30 % by mass of PC at a constant w/b ratio of 0.50 to prepare blended cements. Hydration development of blended cement and compressive strength of Mortars were investigated using chemically bond water and free-lime contents and strength tests respectively. X – Ray diffraction (XRD) and scanning electron Microscopy (SEM) techniques were also utilised in the analysis of Pozzolanic reaction and hydration products. Test results indicates that Water of consistency, setting times for the mixes increased with increase in MK contents, influence of MK on the chemically bond water and free Lime contents of the blended cements were due to its filler and dilution effects and Pozzolanic reaction. The cumulative non-evaporable water and free-lime contents increased by partial replacement of PC with MK due to PC hydration and Pozzolanic reaction. The tested Mortar prepared with blended cements with 30 % PC replacement with MK shows a retardation of strength development with a low value at early ages (7 days) and increased in growth at later ages (28 days). The compressive strength of tested mortar for 90 days curing age for the blended mortar is 31 N/mm2 close to that of control Mortar (35 N/mm2). The results obtained from XRD and SEM analysis indicated increase in Calcium Hydroxide (CH) consumption and Calcium Silicate hydrate (C-S-H) formation in blended cement pastes with curing time. The PC replacement with MK induced changes in Microstructures of blended cement paste and chemical composition of hydration products. These results are potentials for modelling the behaviour of MK-PC blended cements.